Answer :
Answer:
2x^2 + 4x+2
Step-by-step explanation:
f(x) = 2x^2 + x and g(x) = 3x + 2
f(x) + g(x) = 2x^2 + x + 3x + 2
Combine like terms
= 2x^2 + 4x+2
Answer:
[tex]f(x)+g(x)=2x^2+4x+2[/tex]
Step-by-step explanation:
So we have the two functions:
[tex]f(x)=2x^2+x\text{ and } g(x)=3x+2[/tex]
And we want to find:
[tex]f(x)+g(x)[/tex]
So, substitute:
[tex]=(2x^2+x)+(3x+2)[/tex]
Combine like terms:
[tex]=2x^2+(x+3x)+2[/tex]
Add:
[tex]=2x^2+4x+2[/tex]
So:
[tex]f(x)+g(x)=2x^2+4x+2[/tex]
And we're done!